2021
DOI: 10.1002/cyto.a.24487
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic cytometer for white blood cell analysis

Abstract: Despite the wide use of cytometry for white blood cell classification, the performance of traditional cytometers in point-of-care testing remains to be improved.Microfluidic techniques have been shown with considerable potentials in the development of portable devices. Here we present a prototype of microfluidic cytometer which integrates a three-dimensional hydrodynamic focusing system and an on-chip optical system to count and classify white blood cells. By adjusting the flow speed of sheath flow and sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…As the golden approach of detecting single-cell bioelectrical properties, impedance flow cytometry characterizes the bioelectrical properties of single cells leveraging impedance changes caused by cells traveling through a sensing region with confined electric filed lines [5,6]. The key biomedical application of impedance flow cytometry is the classification of blood cells as hematology analyzers where leukocytes are threepart differentiated into granulocytes, monocytes and lymphocytes and five-part differentiated into neutrophils, eosinophils, basophils, monocytes and lymphocytes [26][27][28][29][30].…”
mentioning
confidence: 99%
“…As the golden approach of detecting single-cell bioelectrical properties, impedance flow cytometry characterizes the bioelectrical properties of single cells leveraging impedance changes caused by cells traveling through a sensing region with confined electric filed lines [5,6]. The key biomedical application of impedance flow cytometry is the classification of blood cells as hematology analyzers where leukocytes are threepart differentiated into granulocytes, monocytes and lymphocytes and five-part differentiated into neutrophils, eosinophils, basophils, monocytes and lymphocytes [26][27][28][29][30].…”
mentioning
confidence: 99%
“…Several other research groups in China are also developing novel cytometric technologies. Li et al [13] have recently reported their development of three-dimensional (3D) hydrodynamic focusing system with on-chip optical design to enable white blood cell analysis with a microfluidic cytometer. Wang et al [14] reported their development of 3D cell focusing system with standing acoustic waves on a sheathless microflow cytometer.…”
Section: Light Scattering Spectra Measurements Have Been Demonstratedmentioning
confidence: 99%
“…By shrinking both flow control and optical components, diverse microfluidic FCMs have been developed. Microfluidic FCMs could ideally be highly portable (15–30 L), ,, easy to operate without extensive user training, and utilized for research purposes and point-of-care diagnostics . However, differing from commercial FCMs, which utilized glass as the material for cell flow tubes to ensure optimized optical performance, most microfluidic FCMs utilized polymer materials, such as polydimethylsiloxane (PDMS) and polymethyl methacrylate .…”
Section: Introductionmentioning
confidence: 99%
“…However, only minimizing the flow control part was inadequate to realize portable FCMs as the off-chip optical components still needed to be precisely mounted 20 and accounted for a large portion of the whole volume of FCMs. Embedding important optical components, including the optical fiber 21−23 and lens, 23−26 be highly portable (15−30 L), 5,12,20 easy to operate without extensive user training, 27 and utilized for research purposes 28 and point-of-care diagnostics. 5 However, differing from commercial FCMs, which utilized glass as the material for cell flow tubes to ensure optimized optical performance, 29 most microfluidic FCMs utilized polymer materials, such as polydimethylsiloxane (PDMS) 30 and polymethyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%